Analisis Perbandingan Pengaruh Material Inti Besi Stator dan Rotor Terhadap Efisiensi pada Permanent Magnet Synchronous Generator 18 Slot 18 Pole - Ananda, Thopan Maidia; Gusnita, Novi (Universitas Al Azhar Indonesia, 2023)
A Permanent Magnet Synchronous Generator (PMSG) is a generator whose excitation comes from permanent magnets and not from additional external excitation. The efficiency of the current PMSG model is still low at 73%, and it needs to be increased by selecting better materials for the stator and rotor. This study simulated the use of better materials for the stator and rotor, namely TR52: USS transformer, M27: USS Motor, and Carpenter: Silicon Steel materials. The simulation used the Magnet Ampholytic Software, which is based on the Finite Element Method (FEM). The results of the simulation experiment are as follows. Using the TR52: USS Transformers material obtained the highest efficiency of 77.3%, followed by the M27: USS Motor material at 77.1%, and followed last by the Carpenter: Silicon Steel material at 75.8%.Keywords – Permanent Magnet Synchronous Generator, Finite Element Method, Efisiensi